European Union economies : a comparative study - Somers, Frans (London : Addison Wesley Longman, 1998)
contributors: Richard Bailey; Ian Stone; PJ Drudy; Marisol Esteban; Andrea Fineschi; Milagros Garcia Crespo; Franz Hackl; Markku Kotilaine; Rudi Kurtz; Aranza Mendizabal; Carmela Nicosia; Jan-Evert Nilsson; Friedrich Schneider; Kirk Thomson; Rev. ed of Eu
Keywords: European countries -- Economic conditions; European Union countries -- Economic policy; Finance -- European Union countries